Implant prosthodontics: In vitro testing methods - Almeida, Erika O.; Júnior, Amilcar Freitas; Delben, Juliana A.; Valverde, Guilherme B.; Silva, Nelson R. F. A.; Rocha, Eduardo P. [UNESP]; Coelho, Paulo G. (My University, 2012)
While randomized controlled clinical studies are strongly suggested as the optimal approach to evaluate the performance of biomaterials and design aspects of dental implants and prosthetic components, these studies are at times not economically viable. Thus, well designed in vitro studies associating virtual models via finite element analysis (FEA) and appropriate in vitro laboratory mechanical testing should be utilized as preliminary investigative tools to reduce the number of clinical studies that are needed to fully characterize the performance of a given implant-restorative system. The present chapter describes the computer simulation using FEA and in vitro tests as single-load-to-failure, staircase and step-stress accelerated life-testing utilized to evaluate implant-restoration systems with emphasis to the advantages and potential limitations of each methodology and how the acquired outcomes can be related to the clinical scenario. Major issues and approaches related to the FEA, such as model creation, finite element software, material properties, bone-implant interface, mesh and convergence of the analyses, boundary and loading condition, validation and interpretation of FE modeling and criteria to interpret the results in FEA studies are listed and described. © 2012 by Nova Science Publishers, Inc. All rights reserved.